Methods for Studying and Advancing Deep Learning Models: Dynamics of Platforms, Applications, nd Emerging Research Trends - Kushnareva, Maria (Journal of Social Science and Humanities, 2024)
Deep learning has rapidly emerged as a focal point, captivating both academic research and industrial applications in recent years. This paper provides a concise overview of the pivotal concepts and determinants underpinning the evolution of deep learning. The impact of data augmentation (DA) on deep learning shines through recent demonstrations, leading to heightened accuracy, stability, and mitigated overfitting. Operating within the broader sphere of machine learning, deep learning's prowess lies in its capacity to autonomously uncover intricate patterns and representations from raw data. Its evolution from conventional machine learning approaches has unlocked transformative potential, propelling advancements in areas such as image classification, speech synthesis, and medical diagnosis. However, challenges pertaining to interpretability, data scarcity, and model generalization persist, fostering an active field of research that continually refines deep learning techniques. The ramifications of this technology are profound, as it reshapes industries and fuels innovation, thereby shaping the trajectory of AI-driven solutions. In contrast, strides in image and spectral data analysis have harnessed the power of synthetic data facilitated by sophisticated forward models and generative unsupervised deep learning methods. This paper offers a comprehensive perspective on deep learning techniques, first introducing them at a high level and subsequently delving into their applications in atomistic simulation, materials imaging, spectral analysis, and natural language processing. Across these modalities, we explore theoretical and experimental data applications, prevalent modeling strategies with their strengths and limitations, as well as available software and datasets. The exposition encapsulates six principal deep learning models that dominate contemporary academic research, elucidating their principles and characteristics. Beyond academia, this work examines industrial applications, such as speech and image recognition, artificial intelligence, and anticipates forthcoming trends and challenges in these domains."